The Evolution of Green Consumerism: A Bibliometric Study of Consumer Behavior in the Context of Sustainability - Loso Judijanto (Sciences du Nord Economics and Business, 2025)
This study investigates the intellectual evolution and structural dynamics of green consumerism through a bibliometric analysis of 1,252 publications indexed in the Scopus database from 2000 to 2024. Using VOSviewer, the analysis maps the conceptual structure, author co-citation patterns, and international collaboration networks in the context of sustainable consumption and consumer behavior. The findings highlight green consumerism, sustainable development, green marketing, and consumption behavior as central themes, indicating a strong intersection between behavioral intention models and marketing strategies in driving eco-conscious purchasing. The temporal overlay reveals a shift from early studies on environmental concern and policy to more recent emphases on sustainable consumption, willingness to pay, and environmental economics. Key authors such as Ajzen, Stern, and Dunlap form the theoretical backbone of the field, while countries like the United States, India, and the United Kingdom emerge as dominant contributors in global research collaboration. The study offers insights into the maturity, diversification, and emerging frontiers of green consumerism, paving the way for future interdisciplinary exploration into digital sustainability, behavioral interventions, and systemic policy integration.